Towards a siRNA-containing nanoparticle targeted to breast cancer cells and the tumor microenvironment - Gomes-da-Silva, Lígia C. (2012)
The present work aimed at designing a lipid-based nanocarrier for siRNA delivery towards two cell sub-populations within breast tumors, the cancer and the endothelial cells from angiogenic tumor blood vessels. To achieve such goal, the F3 peptide, which is specifically internalized by nucleolin overexpressed on both those sub-populations, was used as a targeting moiety. The developed F3-targeted stable nucleic acid lipid particles presented adequate features for systemic administration. In addition, the attachment of the F3 peptide onto the liposomal surface enabled an internalization by both cancer and endothelial cells from angiogenic blood vessels that was significantly higher than the one observed with non27 cancer cells. Sequence-specific downregulation of enhanced green fluorescent protein (eGFP) in eGFP-overexpressing human cancer cell lines, both at the protein and mRNA levels, was further observed upon delivery of anti-eGFP siRNA by F3-targeted liposomes, in contrast with the non-targeted counterpart. This effect was highly dependent on the content of poly(ethylene glycol) (PEG), as evidenced by the co32 localization studies between the siRNA and lysosomes. Overall, the present work represents an important contribution towards a nanoparticle with multi-targeting capabilities in breast cancer, both at the cellular and molecular level.